2017
DOI: 10.1038/s41467-017-00283-3
|View full text |Cite
|
Sign up to set email alerts
|

Extrinsic mechanical forces mediate retrograde axon extension in a developing neuronal circuit

Abstract: To form functional neural circuits, neurons migrate to their final destination and extend axons towards their targets. Whether and how these two processes are coordinated in vivo remains elusive. We use the zebrafish olfactory placode as a system to address the underlying mechanisms. Quantitative live imaging uncovers a choreography of directed cell movements that shapes the placode neuronal cluster: convergence of cells towards the centre of the placodal domain and lateral cell movements away from the brain. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
89
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(96 citation statements)
references
References 65 publications
7
89
0
Order By: Relevance
“…The maximum tension was measured on cell/cell interfaces located in the centre of the tissue, perpendicular to the brain surface (Figure c, orange arrow), which is the direction of the passive cell body movements during axonal elongation (Figure b, orange arrow). This map further supports the idea that the cell bodies of the olfactory neurons undergo compression or traction forces (Figures c and d, green arrows) driving their passive movement and the retrograde extension of axonal processes (Figure d) [Breau et al., ]. Future experiments will identify which cells or tissues generate the mechanical forces driving axon extension in this system.…”
Section: Stretch‐induced Axon Growthsupporting
confidence: 79%
See 4 more Smart Citations
“…The maximum tension was measured on cell/cell interfaces located in the centre of the tissue, perpendicular to the brain surface (Figure c, orange arrow), which is the direction of the passive cell body movements during axonal elongation (Figure b, orange arrow). This map further supports the idea that the cell bodies of the olfactory neurons undergo compression or traction forces (Figures c and d, green arrows) driving their passive movement and the retrograde extension of axonal processes (Figure d) [Breau et al., ]. Future experiments will identify which cells or tissues generate the mechanical forces driving axon extension in this system.…”
Section: Stretch‐induced Axon Growthsupporting
confidence: 79%
“…Indeed an elegant study reported that the primordium provides cues ensuring the growth and guidance of the sensory axons [Gilmour et al., ], but it remains unclear whether the migrating primordium mechanically tows the axons through adhesion mechanisms, or serves as a source of chemical cues guiding the growth cones of the axons. Recently, our laboratory discovered that axon growth mediated by extrinsic forces can occur during the early stages of axon elongation in vivo [Breau et al., ]. Using live imaging, we analysed the dynamics of neuronal movements and axon formation in the zebrafish sensory olfactory circuit, which assembles during the morphogenesis of the olfactory placode.…”
Section: Stretch‐induced Axon Growthmentioning
confidence: 99%
See 3 more Smart Citations